Muse Cells Endogenous Reparative Pluripotent Stem Cells (Tokyo : Springer Japan, 2018)
This book provides the first comprehensive account of multilineage-differentiating stress-enduring (Muse) cells, a pluripotent and non-tumorigenic subpopulation of mesenchymal stem cells (MSCs) that have the ability to detect damage signals, migrate to damaged sites, and spontaneously differentiate into cells compatible with the affected tissue, thereby enabling repair of all tissue types. The coverage encompasses everything from the basic properties of Muse cells to their tissue repair effects and potential clinical applications-for example, in acute myocardial infarction, stroke, skin injuries and ulcers, renal failure, and liver disease. An important technical chapter provides a practical and precise protocol for the isolation of Muse cells, which will enable readers to use Muse cells in their own research. In offering fascinating insights into the strategic organization of the body's reparative function and explaining how full utilization of Muse cells may significantly enhance the effectiveness of MSC treatment, the book will be of high value for Ph.D. students, postdocs, basic researchers, clinical doctors, and industrial developers.
Foreword -- Preface -- Chapter 1 The Muse cell discovery; thanks to wine and science -- Chapter 2 Basic characteristics of Muse cells -- Chapter 3 Muse cells are endogenous reparative stem cells -- Chapter 4 Protocols for isolation and evaluation of Muse cells -- Chapter 5 Stem cells and DNA repair capacity: Muse stem cells are among the best performers -- Chapter 6 Immunomodulatory properties and potential therapeutic benefits of Muse cells administration in diabetes -- Chapter 7 The Role of the Mitochondria in the Evolution of Stem Cells, Including MUSE Stem Cells, and Their Biology -- Chapter 8 Acute myocardial infarction, cardioprotection, and Muse cells -- Chapter 9 Application of Muse Cell Therapy to Stroke -- Chapter 10 Muse Cell - A New Paradigm for Cell Therapy and Regenerative Homeostasis in Ischemic Stroke -- Chapter 11 Application of Muse cell therapy for kidney diseases -- Chapter 12 Liver regeneration supported by Muse cells -- Chapter 13 Current cell based therapies in the chronic liver diseases -- Chapter 14 Artificial pigmented-human skin created by Muse cells -- Chapter 15 Muse Cells and Aortic Aneurysm -- Chapter 16 Muse cells and ischemia-reperfusion lung injury -- Chapter 17 Clinical trials of Muse cells -- Chapter 18 Future of Muse Cells.
Biomedical and Life Sciences
text file PDF
Keywords: Human physiology; Stem cells; Regenerative medicine; Tissue engineering; Immunology; Biomedical engineering; Cell physiology